The Coupling of Local Strain and K+‐Ion Release Induced Phase Transition Heterogeneity in Tunnel MnO2. (28th March 2022) - Peng, Haoyang; Xia, Fanjie; Zhang, Chenyu; Zhuo, Haoxiang; Peng, Xin; Song, Peihao; Sun, Congli; Wu, Jinsong
Abstract: The structure and valence transitions in multi‐valent transition metal oxides are closely associated with the intrinsic functionalities that exhibit wide applications in various fields, such as rechargeable batteries, supercapacitors, and catalysis. The internal strain due to intercalated and then released alkali‐ions and defects plays a critical role in tuning the energetically close correlated structures. However, such an effect is still elusive due to its fast dynamics at the atomic scale that requires both high temporal and spatial resolution. Herein, a chip‐based in situ scanning transmission electron microscope investigation is conducted, in which an abnormal tunnel to layered transition within a single MnO2 nanowire is observed. The internal strain initiates a Jahn–Teller active Mn 3+ transition to facilitate the Mn migration, which significantly reduces the Mn migration barrier and kinetically favors this abnormal transition. This work provides an atomistic insight into a strain effect in tuning the multi‐phase and valence transitions in the functional metal oxides, e.g., the phase transition in MnO2 during K + ‐ion extraction for K + ‐ion batteries. Abstract : An abnormal tunnel to layered transition due to their different energy response to strain is observed within a single MnO2 nanowire by in situ STEM. The strain initiates a Jahn–Teller active Mn 3+ transition to facilitate the Mn migration, which significantly reduces the Mn migration barrier and kinetically favors the abnormal transition.